Members of the evolutionarily conserved PMT family of protein O-Mannosyltransferases form distinct protein complexes among themselves - Girrbach, Verena; Strahl, Sabine (The journal of biological chemistry, 2003)
Protein O-mannosyltransferases (PMTs) initiate the assembly of O-mannosyl glycans, an essential protein modification. Since PMTs are evolutionarily conserved in fungi but are absent in green plants, the PMT family is a putative target for new antifungal drugs, particularly in fighting the threat of phytopathogenic fungi. The PMT family is phylogenetically classified into PMT1, PMT2, and PMT4 subfamilies, which differ in protein substrate specificity. In the model organism Saccharomyces cerevisiae as well as in many other fungi the PMT family is highly redundant, and only the simultaneous deletion of PMT1/PMT2 and PMT4 subfamily members is lethal. In this study we analyzed the molecular organization of PMT family members in S. cerevisiae. We show that members of the PMT1 subfamily (Pmt1p and Pmt5p) interact in pairs with members of the PMT2 subfamily (Pmt2p and Pmt3p) and that Pmt1p-Pmt2p and Pmt5p-Pmt3p complexes represent the predominant forms. Under certain physiological conditions, however, Pmt1p interacts also with Pmt3p, and Pmt5p with Pmt2p, suggesting a compensatory cooperation that guarantees the maintenance ofO-mannosylation. Unlike the PMT1/PMT2 subfamily members, the single member of the PMT4 subfamily (Pmt4p) acts as a homomeric complex. Using mutational analyses we demonstrate that the same conserved protein domains underlie both heteromeric and homomeric interactions, and we identify an invariant arginine residue of transmembrane domain two as essential for the formation and/or stability of PMT complexes in general. Our data suggest that protein-protein interactions between the PMT family members offer a point of attack to shut down overall proteinO-mannosylation in fungi.